Kesantunan Direktif Tuturan Guru Untuk MemotivasiSiswa Dalam Amanat Pembina Upacara Di Smp N 1 Karangdowo - Heriyawan, Danis Danang, Prof. Dr. Harun Joko Prayitno, M.Hum (2016)
Danis Danang Heriyawan/A310120109. THE DIRECTIVE POLITNESS OF TEACHERS' SPEECH TO MOTIVATE THE STUDENTS IN MANDATE OF CEREMONY SKIPPER OF SMP N 1 KARANGDOWO. A thesis. Faculty of Education and Teacher Training, University Muhammadiyah of Surakarta. April, 2016. This research is studying about the directive politeness of teachers' speeches to motivate students in the mandate of ceremony skipper of SMP N 1 Karangdowo, Klaten. The aims of this research are (1) descripting the form and the intention of the directive speech and act. (2) Explaining the measurement of the directive speeches and act. This research belonged to the qualitative descriptive research. This research taken the mandate of skipper ceremony as the primary data when giving speech to the students. The data collecting technique used in this research were the technique of recording, observation, and take a note. The data analysis technique in this research used the equal intralingua method, connect and equal the lingual element in a single pattern of language. The triangulation data was used as the technique of data validation in this research. There are 5 type directive speeches and act are 7 sub-KD provided as results from this research placed in SMP N 1 Karangwondo. Involving 30% forces sub-KD, 30% commands of sub-KD,20% prohibits sub-KD, 10% invites sub-KD, 6% remind sub- KD, 2% give suggestion and 2% criticize sub-KD. This research also provided 5 scale of politeness. Covering loss and profit are 18% data, optional are 8% data, indirect are 4% data, authorities is 2% data and the scale of social distance are 4% data. Keywords: directive, pragmatic, unite.